Pore-induced decoupling of crystallographic microstrain and elastic modulus in ?-Ti-16Nb-4Sn alloy - Kaya, Mehmet; Cakmak, Omer; Karakurt, Eyyup Murat; Annac, Ebru Elibol; Kom, Mustafa (Springer Heidelberg, 2026)
This study resolves a fundamental materials physics paradox in porous biomedical alloys: how can increasing crystallographic defects lead to decreased macroscopic stiffness? A beta-Ti-16Nb-4Sn alloy with controlled porosity (approximately 6% to 55%) was fabricated via powder metallurgy. X-ray diffraction analysis reveals that higher porosity amplifies microstrain (from 0.3 & times; 10(-)& sup3; to 0.54 & times; 10(-)& sup3;, + 80%) and dislocation density (from 4.8 & times; 10 & sup1;(4) m(-)& sup2; to 7.8 & times; 10 & sup1;(4) m(-)& sup2;, + 62%) while refining crystallites from approximately 45 nm to 34 nm. Contrary to classical strengthening expectations, compression tests show a drastic 91% reduction in elastic modulus (from 80 GPa to 7 GPa) and 93% reduction in compressive strength (from 1100 MPa to 75 MPa). Quantitative analysis using the Gibson-Ashby scaling law (C-1 = 0.383, C-2 = 0.206) demonstrates a clear decoupling mechanism: the geometric loss of load-bearing capacity due to porosity completely overrides the intrinsic stiffening effect of crystallographic defects. This allows the macroscopic modulus to be independently tuned to bone-matching levels. The efficacy of this approach is validated in vivo, where the low-modulus porous scaffold exhibits superior osseointegration and vascularization compared to its dense counterpart. Our findings establish a novel design principle for orthopedic implants, enabling independent control of microstructure and stiffness through coupled beta-phase stabilization and pore-architecture engineering.
Keywords: beta-titanium; Ti-Nb-Sn; Porosity; Microstrain; Gibson-Ashby model; Elastic modulus decoupling; Osseointegration; Powder metallurgy